Peer Assessment Rating (PAR) Index as an Alternative for Orthodontic Treatment Need Decision in Relation to Angle Classification - Lale Taner; Fatma Deniz Uzuner; Yağmur Çaylak; Zeynep Gençtürk; Emine Kaygısız (Galenos Yayinevi, 2019)
Objective:This study aimed to determine cut-off points for the Peer Assessment Rating (PAR) index in relation with Angle classification to use as an alternative index for the treatment need assessment.Methods:This study included 607 orthodontic patients aged between 9 and 18 years. Angle classification, PAR, and dental aesthetic index (DAI) scores were determined. The DAI was used as the gold standard to evaluate the subjects for treatment need. The receiver operating characteristics (ROC) analysis was used to evaluate the PAR index in relation to treatment need assessed by DAI.Results:The mean PAR scores for Class I, II, and III malocclusions and total sample were 17.54, 14.27, 18.7, and 20.04, respectively. The areas under the ROC of PAR scores in relation to the DAI assessment were found as 68.3% for the total sample, 66.6% Class I, 59.2% Class II, and 71.3% Class III malocclusions. For the total sample, the optimum cut-off PAR score was 14 in relation to DAI assessment. The cut-off scores for Class I, II, and III malocclusions were 13, 11, and 16, respectively, but considering psychosocial aspects, the recommended score is 14 for Class III.Conclusion:The PAR index can be considered to have an acceptable level of validity for the assessment of orthodontic treatment need regarding Angle classification.